Pengukuran Kandungan Senyawa Polisiklik Aromatik Hidrokarbon (PAH) di Pesisir Perairan Celukanbawang, Bali - pratama, Putra; Perwira, Ima Yudha; Sari, Alfi Hermawati Waskita (Current Trends in Aquatic Science; Vol 7 No 1 (2024), 2024)
This study aims to determine the content of Polycyclic Aromatic Hydrocarbons (PAH) in seawater in Celukanbawang waters, Bali. Industrial activities that take place in Celukanbawang waters can affect the quality of the water and marine life around it, and can even have an impact on the environmental pollution of the waters. Data collection was carried out in February-March 2020. The method used in this research is descriptive method, with the seawater sampling method carried out randomly (random sampling) with the number of stations studied as many as 6 stations with a distance of 100 meters from the shoreline. This study also measured DO levels, temperature, pH, and salinity which were carried out directly at the research location and at the Fisheries Science Laboratory, Faculty of Marine Affairs and Fisheries, Udayana University. The results showed that the average value of Polycyclic Aromatic Hydrocarbons (PAH) from the six stations was 0.021 (mg / L). This shows that the levels of Polycyclic Aromatic Hydrocarbons (PAH) in Celukanbawang waters have exceeded the quality standard threshold in accordance with the Regulation of the Governor of Bali No. 16/2016.